Sistem Pengendalian Robot KRSRI Menggunakan Logika Fuzzy Sugeno Orde Nol - Adhitya, Ryan Yudha; Agus Khumaidi; Zindhu Maulana A.P.; Dimas Pristovani R; Mochammad Madhoni Setiawan; M. Dhani Inwanul F; A. Dewana Putra; Semeru Fatkhurrozi A; M. Dhifa Alfitra; Deni Almunawar; Fonda Jiwa Arkananta Tusila; M. Fakhri Ali Mufidz (Jurnal Elektronika dan Otomasi Industri, 2024)
Robots are one of the technological developments that unite several aspects, such as mechanical, electrical, and programs that are interrelated to one another. Currently, the robot has also been competed in a competition with various categories. One of them is the SAR (Search and Rescue) robot competition which is accommodated in the KRSRI (Indonesian SAR Robot Contest). This SAR robot has a mission to save and bring victims to a safe zone. To develop the robot so that it is more optimal, several studies have been carried out using various methods. In this study, the SAR robot was optimized with the Zero Order Fuzzy Sugeno Logic method. In addition, this study uses a sharp sensor as a distance sensor which has better capabilities than ultrasonic sensors. The results show that the time the robot to reach the finish line fluctuates or has various time results for each trial. The conclusion of this experiment is that the Fuzzy Logic method can be applied to SAR robots. Based on the generated robot motion, the robot can move straight without any tendency to the right or left of the trajectory barrier.